The fracture and fragmentation behaviour of additively manufactured stainless steel 316L - Amott, R; Harris, EJ; Winter, RE; Stirk, SM; Chapman, DJ; Eakins, DE (American Institute of Physics, 2017)
Expanding cylinder experiments using a gas gun technique allow investigations into the ductility of metals and the fracture and fragmentation mechanisms that occur during rapid tensile failure. These experiments allow the radial strain-rate of the expansion to be varied in the range 102 to 104 s−1. Presented here is a comparative study of the fracture and fragmentation behaviour of rapidly expanded stainless steel 316L cylinders manufactured from either a wrought bar or additive manufacturing techniques. The results show that in the strain-rate regime studied, an additively manufactured cylinder failed at a higher strain and produced larger fragment widths when compared to cylinders manufactured from a wrought bar. In addition, an investigation into the role of macroscopic elongated voids that were introduced into the cylinder wall, at an angle of 45° to the cylinder radius, was undertaken. A comparison between experimental and simulated results (using the Eulerian hydrocode CTH) was also completed.